2021
DOI: 10.1096/fj.202001581rr
|View full text |Cite
|
Sign up to set email alerts
|

Is Mycobacterium tuberculosis carcinogenic to humans?

Abstract: Tuberculosis (TB) is an infectious disease caused by the bacillus Mycobacterium tuberculosis (Mtb), whereas cancer is a malignant lesion in which abnormal cells divide uncontrollably and destroy body tissue. The fossilized bone records indicate characteristic lesions of tumor and TB from human mummies in ancient Egypt and ancient manuscripts dating back to 3000 BC. 1,2 Reference of TB and tumors is found in Vedas (3000-2500 BC). 3,4

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 178 publications
(498 reference statements)
0
4
0
Order By: Relevance
“…All complications may increase the risk of secondary lung cancer compared with the non-tuberculosis cohort in primary cancer. Some even believe that Mtb is an absolute lung carcinogen, Mtb acts as an initiator and promoter of tumor growth [ 103 ]. As a result, clinicians should consider this in patients with TB infection, because in patients with primary cancer, TB is more likely to cause secondary lung cancer [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…All complications may increase the risk of secondary lung cancer compared with the non-tuberculosis cohort in primary cancer. Some even believe that Mtb is an absolute lung carcinogen, Mtb acts as an initiator and promoter of tumor growth [ 103 ]. As a result, clinicians should consider this in patients with TB infection, because in patients with primary cancer, TB is more likely to cause secondary lung cancer [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological research has shown that patients with TB have an increased risk of being diagnosed with pulmonary cancers with almost a two-fold increase in the risk of lung cancer ( Shiels et al., 2011 ; Luczynski et al., 2022 ). Previous in vitro studies suggested that M.tb has the potential to promote cancerous processes and in the animal model, chronic tuberculosis infection could induce lung cancer in mice ( Roy et al., 2021 ). Several mechanisms may be involved in this process including increased production of inflammatory cytokines which can target anti-apoptotic intracellular signaling pathways in the tumor cells.…”
Section: Potential Roles Of Evs In the Promotion Of Tuberculosis Towa...mentioning
confidence: 99%
“…Given the association between M. tuberculosis and tuberculosis (TB), a substantial volume of literature has arisen regarding the molecular mechanisms underlying this disease, including its possible involvement in carcinogenesis. The Mycobacterium oncogenic hypothesis has garnered increasing attention in recent years [159][160][161]. These studies delve into the intuitive association between TB and lung cancer, drawing on numerous epidemiological investigations that suggest a possible link between M. tuberculosis infection and various malignant tumors, particularly lung cancer.…”
Section: Mycobacteria and Cancer: Focus On Breast Cancermentioning
confidence: 99%